The impact of weather-induced moods on M&A performance - Tunyi Tunyi Abongeh (Economics Letters, 2021)
Unpleasant weather induces negative moods and, consequently, increases managerial risk aversion. We conjecture that this weather-induced risk aversion leads to better M&A performance by constraining managerial hubris, over-confidence and over-payment for targets. Using a large UK sample, we document robust and significant heterogeneity in M&A performance conditional on the weather. Specifically, UK acquirers earn significant positive CARs from deals announced in unpleasant weather but negative CARs otherwise.